A new species of Nemoura (Plecoptera: Nemouridae) from Jiangsu Province, China, with new illustrations for Nemoura nankinensis Wu - Chen, Zhi-Teng; Du, Yu-Zhou (Zootaxa, 2017)
A new species of Nemoura (Plecoptera: Nemouridae), N. fusiformis sp. nov. from Jiangsu Province, China, is described and illustrated. The new species is characterized by a strongly sclerotized large hook formed by outer margin of the outer lobe of the paraproct and by the outer sclerite of cercus with a sub-triangular medial process. The new species is compared with similar taxa. Additionally, supplementary illustrations for N. nankinensis Wu, 1926 are also provided.